Statistical analysis of agarwood oil chemical compound exists in four species of aquilaria - Amir Hussairi, Zaidi; Anis Hazirah ‘Izzati H., Al-Hadi; Siti Mariatul Hazwa, Mohd Huzir; Zakiah, Mohd Yusoff; Nurlaila, Ismail; Almisreb, Ali Abd; Saiful Nizam, Tajuddin; Mohd Nasir, Taib
Aquilaria, renowned for its agarwood, and valued for its aromatic wood and rich resin, finds use in cosmetics, fragrances, incense, and medicine. Identifying the agarwood-producing species among 21 species of Aquilaria is challenging. This study analyzes chemical compounds in agarwood oil from 4 Aquilaria species: Aquilaria beccariana, Aquilaria crassna, Aquilaria malaccensis, and Aquilaria subintegra using gas chromatography-flame ionization detector (GC-FID). Statistical analysis explores compound abundance, employing methods like mean and Z-score tests. This analysis summarizes those 14 compounds that are consistently present based on zero and non-zero observations, and the Z-score test highlights five chemical compounds, with three compounds appearing in both analyses. These compounds can serve as a reference for future studies on Aquilaria species and agarwood oil, enhancing classification efforts.